Direct measurements of the interactions between clathrate hydrate particles and water droplets1. Issue 30 (14th August 2015) - Liu, Chenwei; Li, Mingzhong; Zhang, Guodong; Koh, Carolyn A.
<x xml:space="preserve">Abstract</x> Cyclopentane hydrate particle–droplet interactions and the effects of several fundamental factors have been systematically investigated.